A Multimodal Discourse Analysis of KFC Fried Chicken’s Video Advertisement - Dania, Rahma; Sari, Rosi Kumala (Language Circle: Journal of Language and Literature, 2023)
In recreating new advertisement during the pandemic, the culinary companies, including KFC Indonesia, take full advantage of using Instagram in promoting their brand and product. This study examined the process of how semiotic system create the overall meaning of the advertisement, used in KFC Indonesia’s Instagram video in order to attract costumer. The data of this study were collected from a video advertisement published by KFC Indonesia on Instagram. This study employed descriptive qualitative study.This study analyzed the multimodal elements by using the theory proposed by Anstey and Bull (2010). This study focuses on the analysis of linguistics, visual, gestural and audio analysis of multimodal system occured in the video. The analysis foundthat the combination of linguistics, visual, and gestural elements in the video advertisement of KFC Indonesia could maintain the aim of advertisement to influence the costumers to purchase the products, eventhough it was spesifictly created for pandemic situation.In linguistics analysis, the study found that the video used formal and standard Indonesian language as the script of the video. Further, the language used could deliver the process of informing new policy to the costumer. Meanwhile, the analysis of audio used on the video determined that the use of music and narrator’s voice in the same volume could affect the ambiance of the video. The findings revealed that the video was created to influence the costumer to keep buying the products despite the pandemic by delivering the video advertisement in the Instagram account.